2015
DOI: 10.4172/2161-0487.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Children’s Emotional Development during the First Grade: The Moderating Role of Child Temperament

Abstract: This study investigated the associations between parenting styles (affection, behavioral control, and psychological control) and children's emotional development (emotion expression) during the first grade of primary school, and the moderating role of children's temperament (easy, difficult, and inhibited) in these associations. Mothers and fathers of 152 children responded to a questionnaire concerning their parenting styles and their child's temperament at the beginning of their child's first grade (Time 1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 110 publications
(163 reference statements)
2
17
0
6
Order By: Relevance
“…A few studies have begun to address the possible moderating role of children's personality in associations between parental psychological control and children's maladjustment, but little systematic evidence for such moderating effects has been garnered (e.g. Mabbe, Soenens, Vansteenkiste, & Van Leeuwen, ; Zarra‐Nezhad, Aunola, Kiuru, Mullola, & Moazami‐Goodarzi, ). The current study aims to add to the literature by examining for the first time the moderating role of child personality in associations between daily psychologically controlling parenting and children's daily adjustment.…”
Section: Psychologically Controlling Parentingmentioning
confidence: 99%
“…A few studies have begun to address the possible moderating role of children's personality in associations between parental psychological control and children's maladjustment, but little systematic evidence for such moderating effects has been garnered (e.g. Mabbe, Soenens, Vansteenkiste, & Van Leeuwen, ; Zarra‐Nezhad, Aunola, Kiuru, Mullola, & Moazami‐Goodarzi, ). The current study aims to add to the literature by examining for the first time the moderating role of child personality in associations between daily psychologically controlling parenting and children's daily adjustment.…”
Section: Psychologically Controlling Parentingmentioning
confidence: 99%
“…For example, Zarra-Nezhad et al (2014), found that particularly those children who showed signs of social withdrawal were vulnerable to the negative effects of low maternal affection in terms of externalizing behavior. In another study Zarra-Nezhad et al (2015), reported that high maternal affection predicted subsequently low levels of negative emotions among inhibited children, but not among non-inhibited children, during the first grade. Baer et al (2015) also found that more extreme levels of maternal positive involvement were related to lower levels of social functioning among children with higher levels of harm avoidance (i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, compared to other children, temperamentally vulnerable children have been found to be more affected by their mothers' and fathers' socialization (Belsky & Pluess, 2009). Although some studies have explored the joint effects of shyness (or nearly related but different constructions, such as behavioral inhibition) and parenting behavior on children's developmental outcomes (e.g., Baer et al, 2015;Hane, Cheah, Rubin, & Fox, 2008;Hastings, Rubin, & DeRose, 2005;Kienbaum, Volland, & Ulich, 2001;Lewis-Morrarty et al, 2012;Vreeke, Muris, Mayer, Huijding, & Rapee, 2013;Zarra-Nezhad et al, 2014;Zarra-Nezhad, Aunola, Kiuru, Mullola, & Moazami-Goodarzi, 2015), few longitudinal studies have focused on the development of children's pro-social behaviors (Hastings et al, 2005;Russell, Hart, Robinson, & Olsen, 2003;Zarra-Nezhad et al, 2014). Moreover, the vast majority of previous studies have focused on children younger than school age; thus, little is known about the joint effects of shyness and parenting on the development of children's pro-social behaviors during their critical transition to primary school (Zarra-Nezhad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is understandable when taking into account that mothers are often the primary caretakers, taking primary responsibility for children in families, and spend more time with their children (Lamb and Oppenheim 1989;Renk et al 2003). Thus, their parenting styles may naturally play a more important role in a child's emotional development than the father's parenting does (Zarra-Nezhad et al 2015). Alternatively, perhaps children tend to be more open to maternal than paternal influence (Aunola and Nurmi 2005) because interactions between mother and child are typically characterized by greater responsiveness, warmth and intimate exchanges than interactions between father and child (Collins and Russell 1991).…”
Section: The Moderating Role Of Supportive Parentingmentioning
confidence: 99%